A Close-Knit Bunch: Political Concentration in Turkey's Anadolu Agency through Twitter Interactions. (2nd April 2016) - Irak, Dağhan
ABSTRACT: Through the 13-year period of Justice and Development Party (AKP) governments, the party has developed its own economic and social network, which has created a dominant-party system with hegemonic tendencies. The creation of a pro-government media has constituted the cultural aspect of this transformation, as many mainstream media outlets have been seized by the government and sold to pro-AKP business ventures. Moreover, the state-run media Turkish Radio and Television (TRT) and Anadolu Agency (AA) companies have been subsidized and restructured in line with the government agenda. These public news producers, especially during the most recent term of the AKP government, have been controlled by officials from a small network close to the party leadership. This study explores the political concentration in Turkey's public media by means of an analysis of the Twitter interactions of AA board members, between August 2011 and February 2015.